An in-depth analysis of adult students in blended environments: Do they regulate their learning in an 'old school' way?. (January 2019) - Vanslambrouck, Silke; Zhu, Chang; Pynoo, Bram; Thomas, Valérie; Lombaerts, Koen; Tondeur, Jo
Abstract: Separation in time and place during the learning process reduces the ability of teachers to observe their students' learning behaviours and provide tailored support. This occurs in blended adult education, which challenges students to learn independently. Possessing self-regulation skills is crucial for success in this context. Therefore, the current study aims to address the self-regulation strategies used by adult students in blended environments. A qualitative study that included framework analysis with 16 semi-structured interviews was conducted to explore how students regulated their cognition, behaviour, context and motivation. Results show that they 1) learn by using organising and rehearsal strategies; 2) are flexible regarding time, effort and environment and; 3) report diverse help-seeking strategies. Nevertheless, they preferred offline learning materials and applied few self-motivation strategies. The findings provide tips for teachers to support and promote the students' self-regulation skills and includes tactics such as being an involved role model on forums to facilitate help-seeking processes. Highlights: External people influence student motivation rather than self-motivation strategies. Adult students prefer offline learning materials (e.g. paper syllabus). Organisational and rehearsal strategies are mostly used to learn. Adult students are flexible regarding time, effort and environment. Students use diverse help-seeking strategies and prefer personal, offline help.